2017
DOI: 10.3892/mmr.2017.7878
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and its receptors are involved in hypertensive vascular injury

Abstract: Adipocyte-derived adiponectin (APN) is involved in the protection against cardiovascular disease, but the endogenous APN and its receptor expression in the perivascular adipocytes and their role in hypertensive vascular injury remain unclear. The present study aimed to detect endogenous APN and its receptor expression and their protective effects against hypertensive vascular injury. APN was mainly expressed in the perivascular adipocytes, while its receptors AdipoR1 and AdipoR2 were ubiquitously expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
3
15
0
1
Order By: Relevance
“…Adiponectin is secreted from adipose tissue, and endogenous adiponectin exerts protective effects against hypertensive vascular injury ( 23 ). Previous studies reported that the adiponectin concentration was lower in some cardiovascular diseases ( 24 ), and was reduced in mice subjected to CLP ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin is secreted from adipose tissue, and endogenous adiponectin exerts protective effects against hypertensive vascular injury ( 23 ). Previous studies reported that the adiponectin concentration was lower in some cardiovascular diseases ( 24 ), and was reduced in mice subjected to CLP ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have reported that adiponectin exerts multiple biological effects in different tissues or organs by binding to their receptors [156]. Adiponectin is closely related to the cardiovascular circulatory system [158,159], which is regulated by RAS. Some researches showed that Ang(1-7) supplement significantly increases the levels of adiponectin [28,160], not only in circulation but also in the myocardial [161].…”
Section: Adiponectinmentioning
confidence: 99%
“…Based on the literature, it can be assumed that the levels of adipocytokine mRNA in the AT are not always a complete re ection of their concentration [22]. In this study, PVAT adipocytes of patients with CAD were characterized by the highest level of adiponectin gene expression, yet the lowest concentration in the supernatant compared to adipocyte cultures of other locations.…”
Section: Discussionmentioning
confidence: 81%